Hubungan Karakteristik dan Frekuensi Bermain Tenis dengan Tekanan Darah pada Pemain Tenis Veteran Kota Bengkulu - Alfajri, Oktomi; Kosvianti, Emi; Ramon, Agus; Wati, Nopia (Avicenna: Jurnal Ilmiah, 2024)
Background: Tennis is a sport that makes the heart more active and pumps blood throughout the body, thereby normalizing blood pressure. Bengkulu City Veteran Tennis Players is a club consisting of an age range ranging from 40-60 years. The frequency of playing tennis in one week is 2 to 3 times playing tennis. Method: The research design used in this research uses an analytical observational study. This design uses a cross sectional approach to see the relationship between frequency of playing tennis and blood pressure in veteran tennis players in the city of Bengkulu. Results: The results of the study showed that there was a relationship between playing frequency and blood pressure with a significant value (p) of 0.00. The p value < α = 0.05 which means there is a relationship. A significant value (p) of 0.231 was obtained, the p value was > α = 0.05, which means there is no significant relationship between gender and blood pressure. Obtained a significant value (p) of 0.076, the p value is > than α = 0.05, Ho is accepted or there is no relationship. Conclusion:It is hoped that field tennis players should always regularly and actively play tennis throughout the week to meet the training recommendations from ACSM and the American Heart Association (AHA). Because the results obtained will really provide heart health to veteran tennis players in Bengkulu City.   Keywords: Tennis, Blood Pressure, and Frequency